Regularity Criteria for the Navier-Stokes Equations Containing Two Velocity Components (Journal of Mathematical Study, 2021)
Based on the critical sobolev inequalities in the Besov spaces with the logarithmicform, the regularity criteria in terms of two velocity components for the 3Dincompressible Navier-Stokes equations are improved.